2011
DOI: 10.1177/0022034510387430
|View full text |Cite
|
Sign up to set email alerts
|

Msx1 Mutations

Abstract: Mutations in the transcription factors PAX9 and MSX1 cause selective tooth agenesis in humans. In tooth bud mesenchyme of mice, both proteins are required for the expression of Bmp4, which is the key signaling factor for progression to the next step of tooth development. We have previously shown that Pax9 can transactivate a 2.4-kb Bmp4 promoter construct, and that most tooth-agenesiscausing PAX9 mutations impair DNA binding and Bmp4 promoter activation. We also found that Msx1 by itself represses transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 27 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…The mutation cosegregated with the oligodontia phenotype in this family with complete penetrance. Previous studies have identified more than ten mutations related to nonsyndromic tooth agenesis in MSX1 [ 10 16 , 23 26 ]. MSX1-deficient mice showed a series of abnormalities in skeletal and tooth development, including the absence of incisor tooth buds and developmental retardation of molar tooth buds [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mutation cosegregated with the oligodontia phenotype in this family with complete penetrance. Previous studies have identified more than ten mutations related to nonsyndromic tooth agenesis in MSX1 [ 10 16 , 23 26 ]. MSX1-deficient mice showed a series of abnormalities in skeletal and tooth development, including the absence of incisor tooth buds and developmental retardation of molar tooth buds [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the best characterized positive feedback loop involving MSX2 and a secreted protein is that operating with BMP4: BMP4 induces Msx2 expression and in turn, MSX2 controls Bmp4 (Bei and Maas, 1998 ) (Figure 2 ). Indeed, the Msx2 promoter contains a BMP-responsive enhancer element (Brugger et al, 2004 ) and the Bmp4 promoter contains an Msx (1 and 2) responsive element (Wang et al, 2011 ).…”
Section: Msx2: a Key Element Of The Transcriptional Network Determinimentioning
confidence: 99%
“…It has been demonstrated that transcriptional repression by MSX1 occurs in the absence of DNA-binding sites; the repressor function is attributed to multiple domains in the N- and C-terminal regions of MSX136. In silico analysis studies have indicated that missense mutations affecting MH4 in MSX1 alter the encoded 3D structures of the proteins, specifically by destabilizing the helix-turn-helix motif or altering its protein-DNA interactions3738. Moreover in vitro studies have demonstrated that nuclear localization of MSX1 protein is mediated by the homeodomain37.…”
Section: Discussionmentioning
confidence: 99%
“…In silico analysis studies have indicated that missense mutations affecting MH4 in MSX1 alter the encoded 3D structures of the proteins, specifically by destabilizing the helix-turn-helix motif or altering its protein-DNA interactions3738. Moreover in vitro studies have demonstrated that nuclear localization of MSX1 protein is mediated by the homeodomain37.…”
Section: Discussionmentioning
confidence: 99%